High normal blood pressure in young patients – a disease or a risk factor? - N. P. Lyamina; P. V. Dolotovskaya (Кардиоваскулярная терапия и профилактика, 2005)
Aim. To study correlations between blood pressure (BP) level and autonomous dysfunction symptoms. Material and methods. The study included 84 males aged 18-45, with mean systolic BP (SBP) level of 110-139 mm Hg, and diastolic BP (DBP) level of 70-89 mm Hg. The standard physical and instrumental examination, 24-hour BP monitoring, and modified orthostatic test were performed. Results. In 80% of the patients with high normal (HN) BP, there were some clinical symptoms observed, e.g. headache and vertigo. Circadian BP profile was characterized by increased load index and elevated mean BP during all day, comparing to normotensive subjects. HN BP group was heterogeneous: in 42.3% of cases, BP variability was increased, nighttime BP was abnormally decreased, and hemodynamics reaction in orthostatic test was exaggerated. Conclusion. In young males with HN BP, autonomous dysfunction symptoms, associated with increased BP variability and abnormally increased nighttime BP drop, can be regarded as a complex of early cardiovascular disease predictors.